In the aggregates : forty-two years in the sandbox - Haumesser, Andrew F. (Society for Mining, Metallurgy & Exploration, 2023)
"This book contains a history of aggregates and discusses the importance of the industry to the economy as well as modern society. It describes the exploration techniques, real estate acquisition, permitting, mining and production methodologies, management philosophy, and sustainability. The author's personal experiences are included to enhance the readability and interest in the technical material presented"-- Provided by publisher.
Keywords: Sand and gravel mines and mining.; elektronické knihy; electronic books